Analysis of the Effect of Job Satisfaction, and Job Motivation on Teacher's Work Commitment SMA Santa Maria Kabanjahe - Waldin Malau; Rindi Andika; Suwarno (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
This study aims to determine: (1) Knowing the effect of work motivation on the work commitment of Santa Maria Kabanjahe High School teachers and (2) Knowing the effect of job satisfaction on the work commitment of Santa Maria Kabanjahe High School teachers. The population of this study was the teachers of SMA Santa Maria Kabanjahe, as many as 52 people. Sampling is done proportionally. The research method is path analysis which aims to test theories and obtain information about education. Based on hypothesis testing, it can be concluded: (1) there is a positive influence between work motivation on teacher work commitment of 27.63% (2) there is a positive influence between job satisfaction and teacher work commitment of 7.29%. So to increase the work commitment of teachers, it is necessary to increase work motivation and job satisfaction.